The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The Cambridge Handbook of the Global Work–Family Interface
DOI: 10.1017/9781108235556.031
|View full text |Cite
|
Sign up to set email alerts
|

Family-Supportive Supervision around the Globe

Abstract: Part of the Management Sciences and Quantitative Methods Commons Share feedback about the accessibility of this item.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…From a practical standpoint, an SST may also be promoted because it can involve training a relatively smaller group of supervisors within an organization, while having positive effects for a larger number of employees, and altering aspects of the work culture (e.g., supervisor attitudes; Hammer et al, 2019) that allow for a more supportive environment. Consistent with this perspective, reviews have indicated there are additional beneficial effects resulting from such training (e.g., organizational citizenship behaviors and safety; Hammer et al, 2016; Kossek et al, 2018), which have the potential to further bolster positive employee outcomes because they change psychosocial aspects of the workplace and can therefore reduce stress and increase support.…”
Section: Theoretical Background Of Supportive Supervisor Trainingsmentioning
confidence: 98%
See 1 more Smart Citation
“…From a practical standpoint, an SST may also be promoted because it can involve training a relatively smaller group of supervisors within an organization, while having positive effects for a larger number of employees, and altering aspects of the work culture (e.g., supervisor attitudes; Hammer et al, 2019) that allow for a more supportive environment. Consistent with this perspective, reviews have indicated there are additional beneficial effects resulting from such training (e.g., organizational citizenship behaviors and safety; Hammer et al, 2016; Kossek et al, 2018), which have the potential to further bolster positive employee outcomes because they change psychosocial aspects of the workplace and can therefore reduce stress and increase support.…”
Section: Theoretical Background Of Supportive Supervisor Trainingsmentioning
confidence: 98%
“…For example, previous SST studies have been linked to improved employee job outcomes, reductions in work–family conflict, and improved sleep, particularly when contextual factors are considered (Crain et al, 2014; Crain & Stevens, 2018; Hammer et al, 2011, 2016; Kossek, Pichler, Bodner, & Hammer, 2011; O’Driscoll et al, 2003). Several reviews have indicated there are additional beneficial effects resulting from such training (e.g., organizational citizenship behaviors and safety; Hammer et al, 2016; Kossek, Odle-Dusseau, & Hammer, 2018), which have the potential to further bolster positive employee outcomes. From a practical standpoint, an SST may also be promoted because it can involve training a relatively smaller group of supervisors within an organization, while having positive effects for a larger number of employees, and altering aspects of the work culture (e.g., supervisor attitudes; Hammer et al, 2019) that allow for a more supportive environment.…”
Section: Theoretical Background Of Supportive Supervisor Trainingsmentioning
confidence: 99%
“…In addition to such individual and situational factors, recent theoretical advances have conceptualized FSSB as a dyadic phenomenon, stating that “supervisor-employee dyads are very important to the enactment of work-life support” ( Kossek et al, 2018 , 16). In fact, it has been theorized that supervisors engage in FSSB selectively, such that the extent to which a supervisor supports a specific subordinate depends on features of the particular dyadic relation between the supervisor and subordinate ( Straub, 2012 ; Sargent et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the powerful influence of leaders on their employees' work-family experiences (Kossek et al, 2018), leaders also should not shy away from active family engagement (e.g., discussing their life outside of work and making time for their personal lives). While the book mentions how leaders can be role models and allies, recent research from the U.S., U.K., and Germany further underlines the benefits that global leaders may also personally gain from more active family engagement, involvement, and even work-family conflict (e.g., Dumas & Stanko, 2016;Gloor & Braun, 2020;Morgenroth et al, 2020;Ten Brummelhuis et al, 2014).…”
mentioning
confidence: 99%